Evaluación de la contaminación al acuífero, en la región Morelia-Capula, causada por el impacto de la infiltración de lixiviados generados por el basurero municipal de la ciudad de Morelia - Verduzco Cedeño, Luis Alberto (Universidad Michoacana de San Nicolás de Hidalgo, 2010)
To assess the level of contamination in the Morelia-Capula region, we define the universe of sampling points which we obtained water samples to measure concentrations of physicochemical parameters, metals heavy and isotopic; using field equipment (Manual Tester HANNA Waterproof pH meter) and analysis laboratory, which allowed to obtain network information wells that supply drinking water to the area of study. They were obtained from records of the CNA Operator Agency and Drinking Water, Sewerage and Sanitation Morelia, 14 lithological cuts the study area to correlate laboratory results 40 exploitations evaluated (monitoring density 9.26 km 2 / well); from the above, performed with ArcView 3.2 software thematic maps (isolines) for each parameter evaluated, critical areas with pollution problems regarding trace elements are: Itzicuaro Cerrito (Manganese 186.30 mg / L) Tarehuicho (Iron 527.00 mg / L), Spa Cointzio (Copper 321.20 mg / L), Stone Seat (Zinc 13.80 mg / L), Cointzio (Arsenic 5.85 mg / L) and St Barnabas (Cadmium 0.55 mg / L). With regard to turbidity, color and total dissolved solids, is the southwestern region lot more problems presents, associated with rural environment on which the uses were built; regarding potential hydrogen, higher values were recorded near the dump solid waste which represents basic pH revenue product subsurface leachate.

Para evaluar el nivel de contaminación en la región Morelia-Capula, definimos el universo de puntos de muestreo de los cuales obtuvimos muestras acuosas para medir las concentraciones de parámetros físico-químicos, metales pesados e isotópicos; utilizando equipo de campo (Tester HANNA Waterproof manual pHmetro) y análisis de laboratorio, que permitieron obtener información de la red pozos que suministran agua potable a la zona de estudio. Se obtuvieron de registros de la CONAGUA y el Organismo Operador de Agua Potable, Alcantarillado y Saneamiento de Morelia, 14 cortes litológicos de la zona de estudio para correlacionar los resultados de laboratorio de los 40 aprovechamientos evaluados (densidad de monitoreo de 9.26 km 2 /pozo); a partir de lo anterior, se realizaron con el software ArcView 3.2 mapas temáticos (Isolineas) para cada parámetro evaluado, las zonas críticas con problemas de contaminación en cuanto a elementos traza son: Cerrito Itzícuaro (Manganeso 186.30 mg/L), Tarehuicho (Hierro 527.00 mg/L), Balneario Cointzio (Cobre 321.20 mg/L), Asiento de Piedra (Zinc 13.80 mg/L), Cointzio (Arsénico 5.85 mg/L) y San Bernabé (Cadmio 0.55 mg/L).
Instituto de Investigación en Metalurgia y Materiales. Maestría en Geociencias y Planificación del territorio
Keywords: info:eu-repo/classification/cti/1; IIMM-M-2010-0090; Contaminación; Lixiviados; Basurero; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5135